2011
DOI: 10.1007/s00360-011-0624-9
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of hyper-salinity tolerance in teleost fish: a review

Abstract: Hyper-saline habitats (waters with salinity >35 ppt) are among the harshest aquatic environments. Relatively few species of teleost fish can tolerate salinities much above 50 ppt, because of the challenges to osmoregulation, but those that do, usually estuarine, euryhaline species, show a strong ability to osmoregulate in salinities well over 100 ppt. Typically, plasma Na(+) and Cl(-) concentrations rise slowly or not at all up to about 65 ppt. At higher salinities ion levels do rise, but the increase is small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 68 publications
(97 reference statements)
2
66
0
4
Order By: Relevance
“…Laboratory studies conducted in several euryhaline teleosts, including the black-chinned tilapia, showed a signiWcantly increased branchial NKA subunit expression (and in some species also the subunit) in hypersaline conditions (Jensen et al 1998;Deane and Woo 2004;Tine et al 2008;Gonzalez (2011)). In the European sea-bass D. labrax for example, a "U-shaped" salinity dependency has been shown for the branchial NKA ( subunit) with lowest expression levels at the iso-osmotic point (15 ‰) and highest expression levels at extreme salinities (0 and 50 ‰) (Jensen et al 1998).…”
Section: Na + /K + -Atpase Expression and Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…Laboratory studies conducted in several euryhaline teleosts, including the black-chinned tilapia, showed a signiWcantly increased branchial NKA subunit expression (and in some species also the subunit) in hypersaline conditions (Jensen et al 1998;Deane and Woo 2004;Tine et al 2008;Gonzalez (2011)). In the European sea-bass D. labrax for example, a "U-shaped" salinity dependency has been shown for the branchial NKA ( subunit) with lowest expression levels at the iso-osmotic point (15 ‰) and highest expression levels at extreme salinities (0 and 50 ‰) (Jensen et al 1998).…”
Section: Na + /K + -Atpase Expression and Activitymentioning
confidence: 98%
“…To oVset the loss of water, teleosts need to decrease their branchial water permeability and increase their drinking rate. In a recent review on Wsh physiology of hypersalinity tolerance, Gonzalez (2011) stated that in several species, drinking increases with salinity, but only at a slow rate regarding hypersaline media. Active monovalent ion absorption in the intestine followed by osmotic uptake of water (Ando et al 2003), as well as, higher rates of HCO 3 ¡ secretion is necessary to prevent dehydration and ion load.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity is one of the most important abiotic factors affecting the growth of fishes and has complex and wideranging biological effects (Boeuf and Payan, 2001;Jamil et al, 2004;Gonzalez, 2012;Webb et al, 2012). Cortisol is an important glucocorticoid that functions in the osmotic acclimation and stress response of teleosts (Mommsen et al, 1999;McCormick, 2001;O'Connor et al, 2011;Pankhurst, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The gastrointestinal tract (GI tract) of marine fish plays a critical role in osmoregulation via the process of NaCl coupled fluid absorption [18][19][20][21]. However, the dual role of the intestine, serving hydromineral functions as well as the digestion and absorption of nutrients, is often in conflict and many of the interactions are not well understood [17][18][19][22][23][24][25]. It is known that consumption of large meals of dry aquafeed immediately increase the load of minerals in the GI tract, drastically changing the ionic balance of the intestine [21,24].…”
Section: Introductionmentioning
confidence: 99%